IMPROVING THE COMMUNITY ECONOMY THROUGH UMKM GINGER CRIPS BUSINESS IN RACEK TIRIS VILLAGE, PROBOLINGGO - Rukul Abadi (Universitas Nurul Jadid, 2023)
sugar, ginger, coconut and sesame. Making ginger chips uses the traditional way and requires patience, because the manufacture is quite difficult and requires painstaking, so many people prefer to buy rather than make it themselves. However, this is a big opportunity for ginger chip makers, especially during the month of Ramadan. One of the villages that produces ginger chips is Racek Village. The ingredients for making ginger chips themselves are almost self-harvested, such as coconut and ginger, compared to buying them at the market so that local people use their land. The type of research used in this research is descriptive research using a qualitative approach. The results of this study can be concluded that the business of making ginger chips is reducing unemployment for housewives, and can increase the economy of the people of Racek Village, besides that the natural resources found in Racek Village can be put to good use. and the existence of a ginger chip business in the village of Racek not only improves the economy experienced by the ginger chip makers, but also improves the economy of the surrounding community.